DAMPAK SISTEM KEAGENAN BULOG TERHADAP DISTRIBUSI DAN HARGA GULA KRISTAL PUTIH (GKP) - Lestari Rahayu Waluyati; Jamhari Jamhari (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2010)
This study aimed to determine the impact of Bulog agency’s system to distribution and prices of GKP (2008 and 2009); uses secondary data and interviews of Bulog marketing (agent), PTPN-PT RNI (manufacturer and distributors). Area samples are taken by purposive (Jakarta, Central Java, East Java and Lampung); analysis using tables and graphical analysis. The results showed that the system is in the marketing agency Bulog GKP cause marketing chain shorter because Bulog can distribute directly to distributors medium (D2) and small (D3) and also increased the number of D2 and D3. This agency beneficial for producers (PTPN/PT-RNI)which increase the selling price GKP greater than the increase in the retail price, so that marketing margins down. The market becomes more efficient, so the society surplus received greater. In the wider economy, the system can improve welfare agency indicated by the increase in producer surplus is greater than the decrease in consumer surplus.